2019
DOI: 10.1111/dth.13013
|View full text |Cite
|
Sign up to set email alerts
|

Topical methotrexate 1% gel for treatment of vitiligo: A case report and review of the literature

Abstract: Vitiligo is quite a common hypopigmentary disorder, which may affect both children and adults with important psychological effects due to the well‐known leopard skin‐like appearance. Even if asymptomatic and not life threatening, vitiligo has to be increasingly studied and treated. Hitherto, the efficacy of topical methotrexate in treatment of vitiligo has not been reported. We herein reporting our preliminary observation on the promising efficacy of topical methotrexate in one patient with stable vitiligo. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…MTX is a folate antagonist that appears to decrease the number of T cells producing TNF-α, consequently having anti-inflammatory, immunomodulatory and antiproliferative effects (54). In a recent case report (54) in a patient with stable vitiligo, significant repigmentation was observed following treatment with topical MTX 1% gel applied twice daily for 12 weeks, along with folic acid supplementation. No side effects were reported.…”
Section: Methotrexate (Mtx)mentioning
confidence: 99%
See 1 more Smart Citation
“…MTX is a folate antagonist that appears to decrease the number of T cells producing TNF-α, consequently having anti-inflammatory, immunomodulatory and antiproliferative effects (54). In a recent case report (54) in a patient with stable vitiligo, significant repigmentation was observed following treatment with topical MTX 1% gel applied twice daily for 12 weeks, along with folic acid supplementation. No side effects were reported.…”
Section: Methotrexate (Mtx)mentioning
confidence: 99%
“…No side effects were reported. However, further studies are required to determine the efficacy and safety of MTX (54).…”
Section: Methotrexate (Mtx)mentioning
confidence: 99%
“…Furthermore, case reports and studies using oral MTX in vitiligo reported variable results, including arrested progression, marked skin repigmentation or no significant changes, and when MTX was compared with oral dexamethasone minipulse, both were considered equally effective (67)(68)(69)(70). Recently, a topical formula of MTX was used in a case report with significant improvement in repigmentation of the vitiligo lesion (71). However, further studies are required.…”
Section: Immunopathogenesis Of Vitiligomentioning
confidence: 99%
“…45 Furthermore, topical methotrexate 1% gel twice daily for 12 weeks has been used in one study with significant improvement of the lesion and no local or systemic side effects. 46 …”
Section: Medical Therapymentioning
confidence: 99%